Development and Testing of the ARS Air Scrubber: A Device for Reducing Ammonia Emissions from Animal Rearing Facilities - Moore, Philip A.; Li, Hong; Burns, Robert; Miles, Dana; Maguire, Rory; Ogejo, Jactone; Reiter, Mark S.; Buser, Michael D.; Trabue, Steven (Frontiers in Sustainable Food Systems, 2018)
Ammonia (NH3), dust and odor emissions from animal feeding operations (AFOs) can cause atmospheric pollution and disputes with neighbors. The objectives of this study were to: (1) re-design the ARS Air Scrubber to improve NH3 removal efficiency, (2) conduct full-scale testing of the scrubber under controlled conditions, (3) evaluate the efficacy of various acids for scrubbing NH3, and (4) determine the effects of air flow rate and NH3 concentration on scrubber performance. A full-scale prototype was constructed and a series of experiments were conducted under various conditions. Acid salts, such as aluminum sulfate (alum), sodium bisulfate, potassium bisulfate, ferric chloride and ferric sulfate were found to work as well as strong acids (hydrochloric, phosphoric and sulfuric) for capturing NH3. The efficiency of the scrubber for capturing NH3 decreased as the ventilation rate increased from over 90% at flow rates of 5,097 m3 h−1 to around 55% at 16,141 m3 h−1. However, the mass of N captured by the scrubber tripled as flow rates increased from 5,097 to 16,141 m3 h−1. Similarly, there was a slight reduction in NH3 removal efficiency as inflow NH3 levels were increased from 10 to 75 μL L−1, whereas the mass of N captured increased from 25 g N h−1 to around 200 g N h−1. This technology could result in the capture of a significant amount of the N lost from AFOs, while simultaneously reducing emissions of dust and odors, which would improve the social and environmental sustainability of poultry and swine production.